Land conflicts and social differentiation in eastern Uganda*. Issue 3 (11th August 2017) - Kandel, Matt
ABSTRACT: Rising competition and conflict over land in rural sub-Saharan Africa continues to attract the attention of researchers. Recent work has especially focused on land governance, post-conflict restructuring of tenure relations, and large-scale land acquisitions. A less researched topic as of late, though one deserving of greater consideration, pertains to how social differentiation on the local-level shapes relations to land, and how these processes are rooted in specific historical developments. Drawing on fieldwork conducted in Teso sub-region of eastern Uganda, this paper analyses three specific land conflicts and situates them within a broad historical trajectory. I show how each dispute illuminates changes in class relations in Teso since the early 1990s. I argue that this current period of socioeconomic transformation, which includes the formation of a more clearly defined sub-regional middle class and elite, constitutes the most prominent period of social differentiation in Teso since the early 20th century.